Lung Cancer Staging-A Clinical Practice Review - Ali B. Rueschhoff; Andrew W. Moore; Maykol R. Postigo Jasahui (MDPI AG, 2024)
Lung cancer is the leading cause of cancer-associated death globally. Staging provides classification of the anatomic extent of cancer that is used consistently worldwide. Lung cancer staging is necessary for prognostication, to inform treatment options, and to allow accurate representation in clinical trials. Staging also separates operable from inoperable disease. Since its introduction in the 1970s, the Tumor, Node and Metastasis (TNM) Staging System has undergone significant revisions, with the latest version, the eighth edition, being effective internationally since 2017. Advances in bronchoscopic and thoracoscopic technologies have expanded procedures to diagnose lung cancer and accurately define the anatomic stage. Understanding the advantages and disadvantages of available methods for staging lung cancer is critical to clinician decision making. In patients with lung cancer without distant metastases, the staging of mediastinal lymph nodes determines treatment options. To minimize the risk and cost, the most appropriate method of staging should identify the highest disease stage while carrying acceptable risk. Minimally invasive endoscopic needle techniques to stage the mediastinum are the first choice to assess for metastases in accessible lymph node stations. Surgical techniques are generally reserved for specific clinical situations, including following negative endoscopic needle techniques when suspicion for nodal involvement is high and to assess endoscopically inaccessible lymph nodes. This review provides a concise account of TNM staging of non-small cell lung cancer (NSCLC) and overview of procedures available for the staging of lung cancer.